Effect of crumb rubber origin on asphalt rubber hot mix laboratory performance - Pais, Jorge C. (2001)
Asphalt rubber traditionally has been produced with crumb rubber coming from an ambient grinding process and mostly from car tires. With this product and the binders used in Arizona and California the specifications currently present in ASTM D 6114 have been established. Nowadays relatively new types of crumb rubber are available in the markets namely those that have been produced by cryogenic methods and can then be reprocessed if desired by a further ambient step such as through a crackermill or a Rotormill. During the reprocess stage the crumb rubber undergoes some changes. Furthermore the quantity of truck tires is now extensive and they are seeing their way into the waste flow. The purpose of this paper was to determine mainly to which extent crumb rubber process type affects asphalt rubber concrete properties. Furthermore it was specifically interesting to identify if the blend of cryogenic rubber with rottormill processed cryogenic rubber would yield fatigue properties identical to those obtained with the traditional ambient processed car tires. The effect of crumb rubber process on asphalt rubber hot mix laboratory performance was investigated using flexural fatigue tests.